2018
DOI: 10.1515/jpem-2018-0052
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of cranial MRI findings in girls with central precocious puberty: a systematic review and meta-analysis

Abstract: Background Some pediatric endocrinologists recommend that girls with central precocious puberty (CPP) have cranial magnetic resonance imaging (MRI) performed only if they are younger than 6 years of age. However, no practice guidelines exist. The objective of this review was to assess the frequency of intracranial lesions in girls with CPP. Content We searched six electronic databases (PubMed, Cochrane, Web of Science, SCOPUS, ProQuest, and Dissertation & Theses) from 1990 through December 2015. We included st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 41 publications
1
47
1
1
Order By: Relevance
“…Some studies have shown that the incidence of CNS lesions is very low in girls with CPP who are more than 6 years of age. 20,24 Thus, the authors recommended that only selected girls undergo cranial MRI. There are other studies, however, that have concluded the opposite.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that the incidence of CNS lesions is very low in girls with CPP who are more than 6 years of age. 20,24 Thus, the authors recommended that only selected girls undergo cranial MRI. There are other studies, however, that have concluded the opposite.…”
Section: Discussionmentioning
confidence: 99%
“…Although the vast majority of CPP in girls is idiopathic, rarely, it can be associated with monogenic conditions, tumor formation or other cranial abnormalities [8]. Recent recommendations advise against routine brain MRI in girls with CPP beginning after age 6, as literature reports cranial findings are discovered in a minority of cases of CPP, of which only 1.6% are actionable tumors requiring treatment [9].…”
Section: Discussionmentioning
confidence: 99%
“…Because some of these rates include incidental lesions, the actual prevalence of brain tumors and other pathology requiring intervention is even smaller [34]. A meta-analysis based on 15 studies comprising a total of 1853 patients found an overall rate of abnormal MRIs of 9% which decreased to 7% when only girls with CPP older than 6 years were included (35). Based on these data and in light of discussions regarding the decreasing age of normal puberty, it is hard to justify routine brain MRI scanning in all girls presenting with puberty before the age of 8.…”
Section: Imagingmentioning
confidence: 99%